PERFORMANCE DARI PRESSURE MAINTENANCE UNTUK RESERVOAR YANG SEBAGIAN BATASNYA BERHUBUNGAN DENGAN AQUIFER - Ginting, Mulia
Streamline simulation model is a simulation technique which can be applied to predict the performance of water injection process. The model can be applied if the streamlines outward from a source confined within the desired boundary. This study describes the technique to confine the streamlines and its application to predict performance on the reservoir boundary which have some restricted flow as in the case of partial water encroachment. The distribution of streamlines determined by Lins image wells method. The method essentially determines the necessary rates for a pre-selected set of image wells in order to prevent streamlines from sources (aquifer or injection wells) across the boundaries. By assumption that flow rate of each streamlines (qs,) are constant and equal to fraction obtained by deviding the flow rate of the source by total number of streamlines, performance of each production wells and reservoir can be predicted. Oil flow rate of each production well is determined by subtraction of wells total rate with water flow rate, where water production rate of each well calculated by multiplying and number of streamlines arrived on them. The performance of reservoir, then, determined based on well performance calculation mentioned above.